Pengaruh Komunitas Merek terhadap Word of Mouth - BASALAMAH, FAUZAN MUHAMMAD (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
This research examines the implications of brand community of Honda Vario Club toward the words of mouth of Honda Vario. This research aimed to study the effect of brand community on the words of mouth in Honda Vario Club, and the dimensions of brand community which significantly influence the words of mouth in Honda Vario Club. The data of this quantitative research were collected through questionnaires filled out by members of Honda Vario Club. The result shows that the brand community significantly influences the words of mouth in Honda Vario Club. In addition, the customer-company relationships and customer-brand relationships also significantly influence the words of mouth.